The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21186828
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Receptor Expression in Cancer and Its Multifaceted Role in Oncolytic Adenovirus Therapy

Abstract: Oncolytic adenovirus therapy is believed to be a promising way to treat cancer patients. To be able to target tumor cells with an oncolytic adenovirus, expression of the adenovirus receptor on the tumor cell is essential. Different adenovirus types bind to different receptors on the cell, of which the expression can vary between tumor types. Pre-existing neutralizing immunity to human adenovirus species C type 5 (HAdV-C5) has hampered its therapeutic efficacy in clinical trials, hence several adenoviral vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 113 publications
(172 reference statements)
0
25
0
Order By: Relevance
“…Moreover, the novel AdV-D24-ICOSL-CD40L has been produced to purposefully infect cancer cells through the DSG-2 receptor. Indeed, in order to target tumor cells, the expression of the adenovirus receptor on the tumor cell surface is crucial [ 78 , 79 ]. Hence, it has been reported that different adenovirus serotypes bind various receptors on the cell of which the expression can vary between tumor types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the novel AdV-D24-ICOSL-CD40L has been produced to purposefully infect cancer cells through the DSG-2 receptor. Indeed, in order to target tumor cells, the expression of the adenovirus receptor on the tumor cell surface is crucial [ 78 , 79 ]. Hence, it has been reported that different adenovirus serotypes bind various receptors on the cell of which the expression can vary between tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has been reported that different adenovirus serotypes bind various receptors on the cell of which the expression can vary between tumor types. Moreover, adenovirus 5 infects the cells through the CAR receptor, while adenovirus 3 binds to the DSG-2 and CD46 instead [ 79 ]. Accordingly, in our experiments, the expression level of the primary entry receptors has been assessed in both tested melanoma cell lines: MUG Mel-1 and MUG Mel-2.…”
Section: Discussionmentioning
confidence: 99%
“…Syrian hamster models have been developed as an animal model for oncolytic species C HAdV vectors; however, AdV receptor studies are otherwise based on cell culture models. From a structural biological point of view, among the primary AdV receptors, only CAR and CD46 have solved structures in complex with their adenoviral ligands according to the entries in Protein Data Bank (PDB) database (Kilcher and Mercer, 2014;Brito and Pinney, 2017;Lasswitz et al, 2018;Hensen et al, 2020;Li et al, 2020;Stasiak and Stehle, 2020).…”
Section: Background Adenoviral Receptorsmentioning
confidence: 99%
“…Wild type Ad5 transduces host cells by attaching via the fiber knob domain to coxsackievirus and adenovirus receptor (CAR) and internalizing by endocytosis through the interaction of the conserved RGD sequences of its penton base proteins with αVβ3/αVβ5 integrins. However, expression of CAR is frequently barely detectable in primary tumor cells reducing Ad5 infection 9 13 . Ad5 tropism modification by inserting the RGD-4C peptide in the HI loop of the fiber knob domain enhanced CAR-independent transduction of a wide range of tumor cells of different tissue origin, including glioma 1 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%